Ecotoxicological Risk of Alkaline Sodic Waste on Plant Development - Świdwa-Urbańska, Joanna; Kalisztan, Patrycja (Geomatics and Environmental Engineering, 2019)
The influence of mixtures of soils and Solvay sediments on plant development was investigated under laboratory conditions to explore the possibility of the revegetation of abandoned post-industrial areas. The sodic alkaline wastes used as a substrate in the research come from settling tanks of the former KZS Solvay Works in Cracow. Such sediments are a mixture of different chemical compounds, characterized by high values of pH and salinity that can constitute strong limiting conditions for future reclamation processes of the area. White clover (Trifolium repens L.), was used in this research as a plant indicator representative of common and sensitive species to the toxic effects of soil high alkalinity and salinity. This work examined the effect of soda factory waste pollution, mixed with three types of soils in four variants of soil: waste ratio, on germination rate and root length development as response variables. The results, analyzed statistically, confirm an inhibiting effect of soda wastes on Trifolium repens L. germination with the significant inhibition of early phase of radicle growth and their elongation. Experiments were conducted on Petri dishes and were based on the Zucconi test. Ecotoxicological risk was evaluated by the percentage of relative seed germination (RSG), relative radicle growth (RRG) and calculated index of germination (GI).